2017
DOI: 10.1186/s40657-017-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

Bulbuls and crows provide complementary seed dispersal for China’s endangered trees

Abstract: Background: Different functional frugivores generally exhibit unequal contributions, both in terms of quantity (seed removal) and quality (seedling recruitment), to effective seed dispersal of plant species. However, variations in this dispersal pattern generated by frugivores across different regions are still unknown. Methods:In our study, we evaluated the contributions of two functional frugivore bird groups, the bulbuls (Pycnonotidae) and crows (Corvidae), in both the seed removal and seedling recruitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Heintze's work shows that corvids disperse a broad taxonomic and ecological range of plants through gut passage, and slightly more than half of the taxa are dispersed by nonclassical endozoochory (i.e., through granivory). The importance of classical endozoochory by corvids has adequately been demonstrated by much contemporary research (Nogales et al, 1999;Wenny et al, 2016;Bai et al, 2017). Heintze (1918, p. 29) also wrote: "Magpies, Hooded Crows, Carrion Crows, Rooks, Jackdaws, Ravens, Choughs, Yellow-billed Choughs, and Siberian Jays disperse seeds of pretty much all European trees, bushes, shrubs, and herbs with berries [fleshy fruits]."…”
Section: Discussionmentioning
confidence: 98%
“…Heintze's work shows that corvids disperse a broad taxonomic and ecological range of plants through gut passage, and slightly more than half of the taxa are dispersed by nonclassical endozoochory (i.e., through granivory). The importance of classical endozoochory by corvids has adequately been demonstrated by much contemporary research (Nogales et al, 1999;Wenny et al, 2016;Bai et al, 2017). Heintze (1918, p. 29) also wrote: "Magpies, Hooded Crows, Carrion Crows, Rooks, Jackdaws, Ravens, Choughs, Yellow-billed Choughs, and Siberian Jays disperse seeds of pretty much all European trees, bushes, shrubs, and herbs with berries [fleshy fruits]."…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has demonstrated that the dominant bird species in a network are strongly influenced by their relative abundance and their ability to adapt to different habitats (Muñoz et al 2017;Schupp et al 2017). In the disturbed habitats of this study, bulbul species were abundant and exhibited a generalist behavior in their habitat selection, which likely contributed to their importance in the seed dispersal networks (Bai et al 2017). Furthermore, the study also highlighted the significance of plant species in seed dispersal networks, which are influenced by the availability and characteristics of their fruits.…”
Section: Discussionmentioning
confidence: 60%
“…In the disturbed habitats of this study, bulbul species were abundant and exhibited a generalist behavior in their habitat selection, which likely contributed to their importance in the seed dispersal networks (Bai et al. 2017). Furthermore, the study also highlighted the significance of plant species in seed dispersal networks, which are influenced by the availability and characteristics of their fruits.…”
Section: Discussionmentioning
confidence: 95%
“…In Asia, many natural forests have been transformed to farmlands by local residents, resulting in several natural patches of forest within highly human-disturbed habitats (Foley et al 2005;Haddad et al 2015). Therefore, it is important to understand the effects of land-cover change on plant regeneration in these disturbed habitats (Cordeiro and Howe 2003;Markl et al 2012;Bai et al 2017).…”
Section: Introductionmentioning
confidence: 99%